Assessment of the possibility of using mobile bridges to overcome man-made structures by specialized multi–axle wheeled vehicles - Tropin S.L.; Misinev A.N.; Gnezdilov S.G. (Научно-технический вестник Брянского государственного университета)
The article provides general information about double-support mobile bridges designed for contactless movement of heavily loaded specialized multi-axle wheeled vehicles on top of man–made structures. Also, recommendations are given on substantiating the possibility of their use for solving specific problems. These recommendations contain expressions obtained by the methods of structural mechanics, on the basis of which it is possible to determine not only the required (minimum) camber of the mobile bridge, which is necessary to ensure the normal passage of the vehicle, but also to assess the stress state of the mobile bridge, as well as to determine the nature of the deformation of the mobile bridge when vehicle moves along it. The presented recommendations allow, at a first approximation, to assess the suitability of the available solutions of a mobile bridge for the passage of specialized multi-axle vehicles over mane–made structures, depending on the required span of the mobile bridge and the load from the vehicle on the mobile bridge. The article also provides an example of solving a specific problem on the basis of these recommendations, in accordance with which, when a mobile bridge is spanned 23.4 m and a working load from one axis of the vehicle is equal to 33.5 tons, the required camber is 400 mm, and the highest equivalent stresses will be about 380 MPa.